Formaldehyde Exposure and Its Potential Health Risk in Some Beauty Salons in Kumasi Metropolis - Noah Kyame Asare-Donkor; James Kusi Appiah; Vincent Torve; Ray Bright Voegborlo; Anthony Apeke Adimado (Journal of Toxicology)
Cosmetologists may be potentially exposed to high levels of formaldehyde as a result of their exposure to formaldehyde released from the various cosmetic products used in the beauty salons. In order to assess the exposure of cosmetologists to formaldehyde, the indoor air in sixty beauty salons across the ten submetros in Kumasi were sampled to determine the formaldehyde levels and the associated noncarcinogenic human health risks. Sampling was done using System Service Innovation Incorporation air sampler model 1000i, and the MBTH spectrophotometric method was used for analysis. The mean levels of formaldehyde concentrations ranged from 88.67 to 170.67 µg/m3. Out of the sixty salons sampled, 36 salons had formaldehyde levels above the WHO permissible limit of 100 µg/m3 for an eight-hour working period and also exceeded the 55 and 9 µg/m3 for chronic and acute reference exposure limit, respectively, set by the Office of Environmental Health Hazard Assessment. The results of this study revealed that the number of customers that visit the salon in a week, number of salon services offered, and age of salon had a positive significant correlation with the level of formaldehyde determined in each salon. The health risk study also revealed that about 50% of the salons had hazard quotient (HQ) above the safety limit (HQ = 1) and may, therefore, pose health risks to cosmetologists in these salons. Results from the analysis of the questionnaire revealed that hairdressers in salons that provide the entire range of salon services captured in the study are at higher risk to the effects of formaldehyde.